2012
DOI: 10.1002/pen.22192
|View full text |Cite
|
Sign up to set email alerts
|

A study on electrical and thermal conductivities of ethylene–octene copolymer/expandable graphite composites

Abstract: A series of ethylene–octene copolymer (EOC) composites have been prepared by melt‐mixing with different weight ratios of expandable graphite filler (0–50% by weight). Electrical conductivity [both alternating current (AC) and direct current (DC)] and thermal conductivity studies were carried out. Effect of filler loading and frequency on electrical conductivity was studied. DC conductivity has increased from 1.51 × 10−13 S cm−1 to 1.17 × 10−1 S cm−1. Percolation threshold by DC and also AC methods was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…At the loading level of below 13.3 phr APP, the stringent rating UL-94 V-0 is achieved for samples (3)-(6); however, the amount of APP increases further; the composites do not reach the classification. When APP is replaced by RPM in the same loading level, the stringent rating UL-94 V-0 is achieved for all of samples (8)- (12). The results further suggest that a favorable synergistic effect exists between (APP + RPM) and EG on enhancing the flame-retardant properties of HDPE/EVA blends.…”
Section: Flammability: Limited Oxygen Index and Ul-94 Testmentioning
confidence: 73%
“…At the loading level of below 13.3 phr APP, the stringent rating UL-94 V-0 is achieved for samples (3)-(6); however, the amount of APP increases further; the composites do not reach the classification. When APP is replaced by RPM in the same loading level, the stringent rating UL-94 V-0 is achieved for all of samples (8)- (12). The results further suggest that a favorable synergistic effect exists between (APP + RPM) and EG on enhancing the flame-retardant properties of HDPE/EVA blends.…”
Section: Flammability: Limited Oxygen Index and Ul-94 Testmentioning
confidence: 73%
“…The apparent thermal conductivity of the composites, hereafter called simply thermal conductivity, was measured using experimental setup shown schematically in Figure 1 according to the method described in [20,21]. At the beginning of the measurement, the central brass cylinder (CBC) was annealed to a temperature 45 ∘ C using a hollow cylinder connected to a water thermostat.…”
Section: Methodsmentioning
confidence: 99%
“…To describe the temperature time dependence of the central brass cylinder (Figure 1), the following heat balance equation is used [21]:…”
Section: Calculation Of Thermal Conductivitymentioning
confidence: 99%
“…For example, polyethylene terephthalate-EG-clay nanocomposites with good flame-retardant performances were prepared by melt blending. [22] Svoboda and his coworkers [23] have investigated the effect of different weight ratios of EG on the thermal conductivity and flame retardancy of ethylene-octene copolymer composites. The results demonstrated that EG is an efficient additive which acts as a blowing agent as well as a carbonization agent.…”
Section: Introductionmentioning
confidence: 99%